Seroprevalencia de leptospirosis en pacientes con síndrome febril no palúdico (2023)
Introduction: leptospirosis is a zoonotic disease transmitted by several species of wild and domestic animals, which serve as reservoirs of the causative agent. The disease affects humans from urban and rural areas of the world. Objective: determine Leptospira sp. antibody seroprevalence and dominant serogroups in patients with non-malarial febrile syndrome from Meta Department in Colombia. Methods: across-sectional prospective study was conducted. The study population was all the febrile patients attending a hospital in the city of Villavicencio from May 2013 to June 2014. The paired sera were processed using the microagglutination test with the following serogroups: Australis, Ballum, Bataviae, Canicola, Cynopteri, Panama, Pyrogenes, Sejroe and Semaranga. Diagnostic tests were performed for dengue (IgM and IgG antibody detection by ELISA), rickettsiosis (IgG antibody detection by indirect immunofluorescence), and hantaviral disease (IgG antibody detection by ELISA). Results: of the 100 sera studied, 29 were positive for leptospirosis. The most prevalent serogroups were Canicola and Ballum. Conclusions: prevalence results for leptospirosis show that the disease has been under-recorded in the area. It is thus advisable to include it in the differential diagnosis of febrile syndromes. © 2018, Editorial Ciencias Medicas. All rights reserved.